Influence of pre- and post-slaughter factors on the reduced glutathione content of beef muscles. (February 2017) - Rakowska, R.; Sadowska, A.; Waszkiewicz-Robak, B.
Abstract: The aim of this experiment was to assess the effect of certain factors (muscle anatomy, paternal breed, diet, age at slaughter, castration, process of meat aging and grilling) on the content of reduced glutathione (GSH) in beef. The research material included selected beef muscles acquired from steers and bulls obtained by crossing Polish Holstein-Friesian cows with meat breed bulls (Limousin, Charolais, Hereford). An analysis of ante-mortem factors such as the castration, slaughter age, and fattening of the animals showed no significant effect on the content of GSH (α = 0, 05). On the other hand, the paternal breed of animals was observed to have a significant effect on GSH content. In the study, GSH content significantly increased during meat aging. In contrast, grilling caused a loss approximately 40% of GSH content. Based on the study, it can be concluded that the distribution of GSH in anatomical beef muscles is uneven.